Dukungan Keluarga dan Usia Balita dengan Kejadian Gizi Kurang Pada Balita di Wilayah Kerja Puskesmas Simpang IV Sipin Kota Jambi - Azrimaidaliza; Liya Putri Rahmaniya; Denas Symond (Jurnal Kesehatan Komunitas, 2023)
The problem of malnutrition in a toddler is still faced by developing countries, one of which is the State of Indonesia, including Jambi Province. The incidence of malnutrition is still quite high. The purpose of this study was to determine the relationship between family factors and health services with the incidence of malnutrition in children under five. The type of research is quantitative research with a cross-sectional design. The study was conducted from January to June 2021 in the Simpang IV Sipin Health Center Work Area, Jambi City, with a total sample of 83 children under five. Samples were taken by using a stratified random sampling technique. Primary data collection to the respondent's house was then processed and analyzed using the SPSS program with the Multiple Logistics Regression test. The results showed that the incidence of malnutrition was close to 15%. Family support factor (p-value = 0.007; = 0.292; 95% CI = 0.007-0.045 and p-value = 0.002; = 0.325; 95% CI = 0.012 - 0.051) is a factor associated with the incidence of underweight and short in children. toddlers with a positive relationship direction. Then the factor of toddler age (p=0.019; =-0.243; 95%CI=-0.039 - -0.004) was also associated with stunting in toddlers with a negative relationship. Thus, it is necessary to provide education to families about nutritious food for toddlers to get good growth and development.